Faktor Determinan Kejadian Post Anesthetic Shivering di Instalasi Bedah Sentral RS Pku Muhammadiyah Karanganyar - Nuriyah Yuliana; Doni Nur Setyawan (Jurnal Ners, 2025)
The complications or side effects anesthetic techniques is shivering. Tremor after anesthesia is a body compensation mechanism that causes side effects, such as discomfort and even pain in patients, as well as increased oxygen requirements due to increased muscle activity. This study aims to find determining factors for post-anesthetic shivering in the central operating room of PKU Muhammadiyah Karanganyar Hospital. The research used a cross-sectional design involving post-operative patients. The method used was an observation format adapted from an instrument developed and validated by Crossley, A. W. and Mahajan, R.P. The results showed that age, environmental temperature, and operating time were factors that influenced PAS (p <0.05), while gender, type of anesthesia and BMI did not influence the occurrence of post-anesthetic shivering (p > 0.05). Conclusion: surgery time is the main factors influencing the occurrence of post- anesthetic shivering. Suggestion: Pay attention to the factors that cause shivering in patients to be able to predict the possibility of shivering in patients and treat patients who experience post-operative shivering